Optimizing Tobacco Advertising Bans in Seven Latin American Countries: Microsimulation Modeling of Health and Financial Impact to Inform Evidence-Based Policy - Bardach, Ariel Esteban (2021)
Introduction: In Latin America, tobacco smoking prevalence is between 6.4% and 35.2%. Governments have been making efforts to support the regulation of advertising and, in many cases, banning advertising and promotion of tobacco altogether. The objective of this study was to evaluate the potential impact on health and economic outcomes of optimizing a ban on tobacco advertising and sponsorship in Argentina, Bolivia, Brazil, Chile, Colombia, Mexico, and Peru. Methods: We built a probabilistic microsimulation model, considering natural history, direct health system costs, and quality of life impairment associated with main tobacco-related diseases. We followed individuals in hypothetical cohorts and calculated health outcomes on an annual basis to obtain aggregated 10-year population health outcomes (deaths, events, healthy years of life) and costs. To populate the model, we performed a rapid review of literature to calculate intervention effectiveness. Results: With current policies, over 10 years, in Argentina, Bolivia, Brazil, Chile, and Colombia a total of 50,000 deaths and 364,000 disease events will be averted, saving $7.2 billion. If the seven countries strength-ened their policies and implemented a comprehensive ban with 100% compliance, 98,000 deaths and 648,000 events would be averted over 10 years, saving almost $15 billion in healthcare costs. Conclusions: Optimizing a ban on tobacco advertising and sponsorship would substantially reduce deaths, diseases, and health care costs attributed to smoking. Latin American countries should not delay the full implementation of this strategy.